2021
DOI: 10.1111/cura.12405
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Environmental Acidity in Storerooms of Natural History Collections

Abstract: Outdoor and indoor pollutants can affect the conservation of natural history collections. As a first approach to this question, environmental acidity around specimens in the collections of the Natural Science Museum of Barcelona and Botanic Institute of Barcelona (MCNB‐IBB) was measured. Measurements were taken using optical sensors in a number of different places: inside and outside buildings, in storerooms, on store cases and cabinets and in containers in three collections. All acidity measurements fell with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, acidic emissions are not connected to this kind of protective paper. Previous results obtained by checking with optical pH sensors in special storage materials for museum objects indicated that they maintain neutral conditions in their surroundings for a long time [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, acidic emissions are not connected to this kind of protective paper. Previous results obtained by checking with optical pH sensors in special storage materials for museum objects indicated that they maintain neutral conditions in their surroundings for a long time [39].…”
Section: Discussionmentioning
confidence: 99%